2020
DOI: 10.1088/1361-6463/ab7d67
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous current–voltage and impedance behaviour in doped Poly 3-methylthiophene devices

Abstract: Current–voltage (I–V) and impedance measurements are performed on electrochemically-doped poly(3-methylthiophene) (P3MeT) devices in metal/polymer/metal sandwich geometry. The detailed investigation shows the presence of negative differential resistance (NDR) in the sandwich devices with different metals in action as substrate and top electrode. It is found that the reiteration of I–V measurements significantly enhances the NDR. The P3MeT devices shows a considerable switching behaviour with ON to OFF ratio va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…At the same time, it is absent in positive bias. , Further, the change in R 2 values from Table T2 also demonstrates the RS behavior ascribed to conducting filament formation in the TiO 2 -NS as described in the previous section. The appearance of the long elongated tail in the Cole–Cole plot with positive bias is due to the NDR feature in I – V measurements as reported previously by our group. …”
Section: Resultssupporting
confidence: 75%
“…At the same time, it is absent in positive bias. , Further, the change in R 2 values from Table T2 also demonstrates the RS behavior ascribed to conducting filament formation in the TiO 2 -NS as described in the previous section. The appearance of the long elongated tail in the Cole–Cole plot with positive bias is due to the NDR feature in I – V measurements as reported previously by our group. …”
Section: Resultssupporting
confidence: 75%
“…From I-V fitting and previous reports, it is evident that the conduction mechanism involved in doped P3MT devices is by trapping and de-trapping of charge carriers across the polymer/electrode interface and bulk. NDR in PF 6 − doped P3MT is previously studied by varying carrier density, and work function of the electrode, and observed that NDR in polymer devices is due to the trapping and de-trapping of charge carriers [14,15]. The process of de-doping enhances the NDR in P3MT, is due to long-lived traps present in the device, and is an inherent property of the de-doped P3MT device.…”
Section: Methodsmentioning
confidence: 99%
“…Ag is used as top contact to complete the device geometry SS/P3MT/Ag. This de-doped P3MT device show NDR, and is tunable and controllable by various external parameters like work function of the electrode, dopants and doping concentration, applied voltage, and sweep direction [14,15]. In this study, current-voltage measurement is carried out for the P3MT device de-doped for 30 seconds to probe the NDR and charge transport mechanism in the device.…”
Section: Introductionmentioning
confidence: 99%